Reliability and validity of the brief COPE scale (english version) among women with breast cancer undergoing treatment of adjuvant chemotherapy: A Malaysian study - Yusoff, Nasir; Low, Wah Yun; Yip, Cheng Har (Malaysian Medical Association, 2010)
This paper validates the Brief COPE Scale in Malaysian women with breast cancer. Test-retest evaluation was undertaken at two/three weeks and ten weeks following surgery. Internal consistencies ranged from 0.25 to 1.00. Meanwhile, the Intraclass Correlation Coefficient (ICC) ranged from 0.05 to 1.00. Sensitivity of the scale was indicated by the mean differences as observed in most of the domains with Effect Size Index (ESI) ranged from 0 to 0.53. Significant differences between mastectomy and lumpectomy were observed for Active coping, Planning and Acceptance. Brief COPE Scale showed fairly good reliability and validity.